Improve the efficiency of using the university’s facebook fanpage - Tran, Anh Tung; Tran, Quang Cảnh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The objective of this study is to find and quantify the influence of factors on the engagement of the Facebook Fanpage of Generation Z. The study uses the partial structural equation model (PLS-SEM). The results of the link analysis show that the interaction of the brand, the interaction between customers has a positive impact on the perception of entertainment value of users on the Facebook Fanpage page; Quality content, brand interaction, and emotions have a positive impact on users’ perception of pragmatic value on Facebook Fanpage; Recreational values, pragmatic values have a positive impact on the user’s feedback behavior on the Facebook Fanpage; Recreational values and pragmatic values have the same impact on the spreading engagement behavior of users on the Facebook Fanpage. Pragmatic values have a positive impact on the collaborative behavior of users on the Facebook Fanpage.